2022
DOI: 10.1038/s41598-022-20181-z
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive sensibility and body satisfaction in pregnant and non-pregnant women with and without children

Abstract: Pregnancy is a time of great physical and psychological change. As well as prominent changes in the external appearance of the body, such as the baby bump, there are also substantial changes taking place within the body. Our awareness of, and attention towards, internal bodily signals (interoception) is thought to have a direct impact on how we feel about our bodies. Therefore, understanding how our experience of these interoceptive signals might change during pregnancy may have important implications for mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 82 publications
0
14
1
Order By: Relevance
“…One notable participant variable that was hypothesised to affect body image dissatisfaction in pregnancy is gravidity. However, only three studies analysed the effect of gravidity [ 31 , 55 , 64 ]; two of these studies found that women in their first pregnancy (primigravidae) have lower body dissatisfaction than multigravidae (M = 5.76 / 6.01 [ 31 ] and M = 139.2 / 143.8 [ 55 ] for primigravidae and multigravidae, respectively), whereas the third study [ 64 ] found primigravidae had slightly higher body dissatisfaction (M = 9.61) than multigravidae (M = 7.01). Due to the other fourteen studies not reporting separate means for gravidity (N=8; [ 12 , 14 , 56 58 , 62 , 65 67 ]), not reporting gravidity (N=3; [ 36 , 59 , 63 ]), or only testing primigravidae (N=3; [ 60 , 61 , 70 ]) no statistical analysis was possible within this meta analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One notable participant variable that was hypothesised to affect body image dissatisfaction in pregnancy is gravidity. However, only three studies analysed the effect of gravidity [ 31 , 55 , 64 ]; two of these studies found that women in their first pregnancy (primigravidae) have lower body dissatisfaction than multigravidae (M = 5.76 / 6.01 [ 31 ] and M = 139.2 / 143.8 [ 55 ] for primigravidae and multigravidae, respectively), whereas the third study [ 64 ] found primigravidae had slightly higher body dissatisfaction (M = 9.61) than multigravidae (M = 7.01). Due to the other fourteen studies not reporting separate means for gravidity (N=8; [ 12 , 14 , 56 58 , 62 , 65 67 ]), not reporting gravidity (N=3; [ 36 , 59 , 63 ]), or only testing primigravidae (N=3; [ 60 , 61 , 70 ]) no statistical analysis was possible within this meta analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review and meta-analysis of 17 studies compared body image dissatisfaction in pregnant women (total 5200 responses) to women who were not pregnant (total 4172 responses), across 13 between participant design studies [ 14 , 36 , 55 , 57 60 , 62 , 63 , 65 67 , 70 ] and 4 within participant design studies [ 12 , 31 , 56 , 64 ]. The main statistical analysis on a group level showed that women’s body image dissatisfaction was not statistically different during pregnancy compared with when not pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations